KINERJA SOSIAL DAN KINERJA KEUANGAN PERUSAHAAN (LITERATUR REVIEW) - Anggita Langgeng (Universitas PGRI Madiun, 2013)
This paper discusses the relation of corporate social performance with financial performance. This paper is a literature review of research types. With reference to the stakeholder theory, firm with good social performance is expected to be able to accommodate the interests of the stakeholders, so as to have a good relationship from the external environment. With a good relationship with its stakeholders expect corporate managers are able to manage the company more efficiently, have the convenience of the source of funding, have low business risk and have a good appreciation of the market value. From the study of literature to some previous studies it can be concluded that corporate social performance will have a positive impact on the financial performance of the company.